Pengaruh Amerika Serikat dalam Budaya Perfilman Korea Selatan 1950-an: Madame Freedom Karya Han Hyung-mo - Khaliya, Meutia; Setiawan, Agus (Universitas Hamzanwadi, 2023)
In the 1950s around the Korean War, the United States provided a lot of assistance to South Korea, including in the field of film. Hollywood films are increasingly influencing Korean cinema, including films by Han Hyung-mo who is considered one of the pioneers in South Korean cinema, especially after he released the film Madame Freedom. Therefore, the formulation of the problem in this study is what was the role of the United States in South Korean films in the 1950s and how was the influence of the United States included in the film Madame Freedom. This study uses the historical method with four stages, namely heuristics, source criticism, interpretation, and historiography. The purpose of this study is to show the influence of the United States on South Korean film culture in the 1950s. The results of this study show that the United States exerts its influence through films by importing Hollywood films and facilitating various South Korean film needs through related US institutions. The influence of the United States on South Korean film in the 1950s then took the form of the values of modernity and Cold War cosmopolitanism from the United States in all aspects of the film.Ketika Perang Korea terjadi pada tahun 1950 sampai 1953, Amerika Serikat memberikan banyak bantuan bagi Korea Selatan, termasuk dalam bidang perfilman. Film-film Hollywood pun semakin mempengaruhi perfilman Korea, termasuk film-film karya Han Hyung-mo yang dianggap sebagai salah satu pionir dalam perfilman Korea Selatan, terutama setelah ia merilis film Madame Freedom. Oleh karena itu, rumusan masalah dalam penelitian ini adalah bagaimana peran Amerika Serikat dalam perfilman Korea Selatan pada tahun 1950-an dan bagaimana pengaruh Amerika Serikat yang masuk dalam film Madame Freedom. Penelitian ini menggunakan metode sejarah dengan empat tahapan, yaitu heuristik, kritik sumber, interpretasi, dan historiografi. Tujuan dari penelitian ini adalah untuk menunjukkan pengaruh Amerika Serikat dalam budaya perfilman Korea Selatan pada tahun 1950-an. Hasil penelitian menunjukkan bahwa Amerika Serikat memasukkan pengaruhnya melalui film dengan cara mengekspor film-film Hollywood dan memfasilitasi berbagai kebutuhan perfilman Korea Selatan melalui lembaga-lembaga Amerika Serikat yang terkait. Pengaruh Amerika Serikat terhadap perfilman Korea Selatan pada tahun 1950-an kemudian berupa nilai-nilai modernitas dan kosmopolitan Perang Dingin dari Amerika Serikat dalam seluruh aspek film.